1999
DOI: 10.1046/j.1365-2648.1999.00957.x
|View full text |Cite
|
Sign up to set email alerts
|

Predialysis education helps patients choose dialysis modality and increases disease‐specific knowledge

Abstract: the predialysis group education programme enabled patients to choose dialysis modality to achieve an understanding of their illness and its treatment. It also provided the possibility of informal support by fellow patients and health professionals. The study emphasizes the special needs of elderly patients and we recommend that education programmes are tailored to their requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 22 publications
8
47
0
8
Order By: Relevance
“…It is likely that the system in Singapore-in which most medical services, including pre-dialysis education, are mostly feefor-service, with only limited financial support from the government-may be hindering well-informed decisions. As shown in other settings, implementation of reimbursement is likely to improve patient knowledge of dialysis, thus helping to achieve an informed patient decision for a dialysis modality, which is linked to improved rates of PD uptake (14,47,49,50,53). However, more work is needed to document pre-dialysis education utilization rates in relation to PD uptake and penetration rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that the system in Singapore-in which most medical services, including pre-dialysis education, are mostly feefor-service, with only limited financial support from the government-may be hindering well-informed decisions. As shown in other settings, implementation of reimbursement is likely to improve patient knowledge of dialysis, thus helping to achieve an informed patient decision for a dialysis modality, which is linked to improved rates of PD uptake (14,47,49,50,53). However, more work is needed to document pre-dialysis education utilization rates in relation to PD uptake and penetration rates.…”
Section: Discussionmentioning
confidence: 99%
“…Carefully planned and timed pre-dialysis education is therefore critical in clarifying the misconceptions (46)(47)(48)(49)(50)(51). It is imperative to revisit or review how to best cater for the decisional support needs of patients and then to design patient resources and pre-dialysis programs that are sufficiently proactive to engage patients in making informed decisions about dialysis modality, while eliciting and targeting misperceptions and misunderstandings.…”
Section: Discussionmentioning
confidence: 99%
“…Nonsteroidal anti-inflammatory drug (NSAID) avoidance education in patients at risk for AKI increased knowledge of NSAID-associated risks and patient-reported intentions to limit NSAID use (5). CKD patient education programs may defer dialysis initiation (6), increase use of self-care-based dialysis modalities (7,8), lengthen survival on dialysis (9)(10)(11), and improve overall mood and feelings of good health (12). National programs and CKD care guidelines uniformly recommend patient education as a critical component of care (13)(14)(15)(16).…”
Section: Benefits Of Patient Educationmentioning
confidence: 99%
“…Moreover, the need for adequate health-and illnessrelated information is among patients' basic needs, the fulfillment of which can give them senses of peace and safety (24). Different studies demonstrated the positive effects of patient and family education on patient outcomes (25)(26)(27)(28). A study also showed that education and counseling alleviate hemodialysis patients' and their family members' concerns and discomfort (29).…”
Section: Introductionmentioning
confidence: 99%